Gallic and Hesperidin Ameliorate Electrolyte Imbalances in AlCl3-Induced Nephrotoxicity in Wistar Rats - Tajudeen Olabisi Obafemi (Biochemistry Research International)
Nephrotoxicity is usually characterized by inefficiency of the kidney, thereby causing disruptions to electrolyte balance and blood acidity. This study aimed to evaluate the effect of hesperidin and gallic acid on serum electrolytes and ion pumps in Wistar rats subjected to aluminum chloride (AlCl3)-induced nephrotoxicity. Thirty Wistar rats were randomly divided into six groups of five animals apiece. Group one served as the negative control and received distilled water while the study lasted. Animals in groups 2–4 received 100 mg/kg/day AlCl3 throughout the study. Animals in groups 3 and 4 were also administered 100 mg/kg/day gallic acid and 100 mg/kg/day hesperidin, respectively. Groups 5 and 6 were treated with 100 mg/kg/day gallic acid only and 100 mg/kg/day hesperidin only, respectively. Treatments were administered orally via gavage for 28 days with distilled water as the vehicle. Animals were sacrificed after which levels of potassium, calcium, magnesium, phosphate, chloride, and bicarbonate ions were evaluated in the serum, while activities of Na+/K+ and Ca2+/Mg2+ ATPases were determined in kidney homogenate. Results showed that AlCl3 significantly (p<0.05) inhibited activities of Na+/K+ and Ca2+/Mg2+ ATPases in addition to increasing serum levels of potassium, calcium, phosphate, and chloride, with concomitant decrease in serum levels of magnesium and bicarbonate. However, coadministration of AlCl3 with either gallic acid or hesperidin ameliorated all the disruptions caused by AlCl3. It could be concluded that gallic acid and hesperidin could be relevant in managing electrolyte imbalances and acidosis occasioned by kidney dysfunction.